Activation of 5-HT2A/2C receptors reduces the excitability of cultured cortical neurons. (6th October 2016) - Hu, Lingli; Liu, Chunhua; Dang, Minyan; Luo, Bin; Guo, Yiping; Wang, Haitao
Highlights: DOI depresses spontaneous firing of cortical neurons, mimicking the effect of serotonin. DOI depresses current-evoked firing and increases neuronal input resistance. HCN channels account for DOI-induced increase of input resistance, but not for the decrease of spontaneous firing. DOI differentially affects mEPSCs and mIPSCs. Abstract: The abundant forebrain serotonergic projections are believed to modulate the activities of cortical neurons. 5-HT2 receptor among multiple subtypes of serotonin receptors contributes to the modulation of excitability, synaptic transmissions and plasticity. In the present study, whole-cell patch-clamp recording was adopted to examine whether activation of 5-HT2A/2C receptors would have any impact on the excitability of cultured cortical neurons. We found that 2, 5-Dimethoxy-4-iodoamphetamine (DOI), a selective 5-HT2A/2C receptor agonist, rapidly and reversibly depressed spontaneous action potentials mimicking the effect of serotonin. The decreased excitability was also observed for current-evoked firing. Additionally DOI increased neuronal input resistance. Hyperpolarization-activated cyclic nucleotide-gated cationic channels (HCN) did not account for the inhibition of spontaneous firing. The synaptic contribution was ruled out in that DOI augmented excitation and attenuated inhibition to actually favor an increase in the excitability. Our findings revealed that activation of 5-HT2A/2C receptors reduces neuronal excitability, which would deepen our understanding of serotonergic modulation of cortical activities.